2016
DOI: 10.1128/jvi.03159-15
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Microparticle Nanoscale Silicon Dioxide as an Adjuvant To Boost Vaccine Immune Responses against Influenza Virus in Neonatal Mice

Abstract: Neonates are at a high risk of infection, but vaccines are less effective in this age group; tailored adjuvants could potentially improve vaccine efficacy. Increased understanding about danger sensing by the innate immune system has led to the rational design of novel adjuvants. But differences in the neonatal innate immune response, for example, to Toll-like receptor (TLR) agonists, can reduce the efficacy of these adjuvants in early life. We therefore targeted alternative danger-sensing pathways, focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Antibodies (IgG) specific to influenza H1N1 in the sera were measured using a standardized ELISA . Briefly, MaxiSorp 96‐well plates (Nunc, Roskilde, Denmark) were coated with 1 μg/ml surface proteins or a combination of anti‐murine λ and κ light‐chain‐specific antibodies (AbDSerotec, Oxford, UK) and incubated overnight at 4°.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…Antibodies (IgG) specific to influenza H1N1 in the sera were measured using a standardized ELISA . Briefly, MaxiSorp 96‐well plates (Nunc, Roskilde, Denmark) were coated with 1 μg/ml surface proteins or a combination of anti‐murine λ and κ light‐chain‐specific antibodies (AbDSerotec, Oxford, UK) and incubated overnight at 4°.…”
Section: Methodssupporting
confidence: 74%
“…Another study using CpG as an experimental adjuvant has also shown reduced effect of the adjuvant in aged mice . Based on our previous studies, we know that antibody is a critical correlate of protection in mouse models of influenza . But we have recently confirmed the role of CD8 T cells in the resolution of influenza infection, and there are known age‐dependent effects on T cells, so targeting T cells may be more effective in the elderly; for example a peptide vaccine coupled to flagellin that induced T cells was protective in aged mice.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…While we didnot dissect the correlates of protection in the current study, in other studies the strongest correlate protection is IgG and we observed that immunization induced an influenza-specific IgG response. In addition to IgG, we have recently observed a role for IgA in both human ( 24 ) and mouse ( 28 ) challenge studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nanoparticles have been used as adjuvants for enhancing the immunogenicity of protein-based influenza vaccines in mice (Petukhova et al 2013;Neuhaus et al, 2014;Ross et al, 2014;Russell et al, 2016) and chickens (Asl Najjari et al, 2015;Khalili et al, 2015). Sliver nanoparticles with polyethylene glycol were also used to formulate plasmid DNA encoding H5N1 influenza virus hemagglutinin (HA) gene to assess humoral and cellular immune responses in chickens (Jazayeri, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%